Kaji Eksperimental Performansi Alat Pengering Tenaga Surya Tipe Kabinet Jenis Pemanasan Langsung Untuk Pengeringan Pisang - Mainil, Rahmat Iman; Surya, Ahmad; Aziz, Azridjal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Open sun-drying was commonly used to dry the bananas. In fact, bananas were spread on bamboo’s tray and exposed to solar radiation without any covers. The banana usually contaminated by insects, animals and dusts which can make the bananas have a low quality. Therefore, an appropriate dryer is needed to overcome this problem. Solar dryer cabinet type was considered as an alternative device. This study was conducted to observe the performance of the solar dryer cabinet by experimental method. A direct solar dryer cabinet was constructed. The dryer consists of solar collector, drying chamber, glass cover and six racks. The drying time was 8 hours. Open-sun drying was also running in the same time as comparison. 3 kilograms banana were dried and take place on six racks. Solar dryer cabinet type gives the maximum temperature of 62,9 °C inside and 31,9 °C outside. Solar dryer cabinet has reduced the mass of banana approximately 49,6 % than initial mass. With open-sun drying could reduce approximately 25,6 % than initial mass. The results show that the banana which dried with solar dryer cabinet has produce brown colour, sweet taste and thin shape than open-sun drying. Beside that, the drying rate was also faster than open-sun drying. The quality of drying was better when using solar dryer cabinet type than open-sun drying.Keywords : Drying, Banana Drying, Solar Dryer.